Causes of chronic malnutrition in children under five years of age in the district of José María Arguedas - Andahuaylas - Quispe Hoyos, Betzabe Astrid (2025)
Chronic malnutrition is characterized by a delay in a person's growth, generally caused by factors present from an early age. The objective of this research was to identify the causes of chronic malnutrition in children from 0 to 5 years of age in the district of José María Arguedas, province of Andahuaylas. Using a phenomenological, qualitative and descriptive approach. A sample of five families with children under five years of age was selected. To determine the causes, interviews were conducted with parents to assess their knowledge and practices regarding the nutritional feeding of their children. The results indicate a lack of knowledge on the part of the mothers about the nutritional values of the food they provide to their children. It is concluded that the main causes of chronic malnutrition in the population studied are lack of knowledge of the nutritional value of food, low socioeconomic level, lack of adequate sanitation and lack of health education.